The significance of variable order in assessing the effect of perceived parental knowledge and peer deviance on participant delinquency: a replication and extension - Walters, Glenn D. (Crime & delinquency, 2018)
The current study sought to replicate and extend an earlier investigation on mid- to late-adolescent delinquent males to a school-based sample of mixed-gender early- to midadolescents. Two pathways—one running from parental knowledge to peer deviance to participant delinquency and the other running from peer deviance to parental knowledge to participant delinquency—were tested in a group of 597 children (290 boys, 307 girls) from the Illinois Study of Bullying and Sexual Violence (ISBSV). The results of a comparison mediation analysis revealed that consistent with prior research, the knowledge-initiated pathway achieved significance but the peer-initiated pathway did not. These findings suggest that perceived parental knowledge has its greatest impact on delinquency indirectly by way of its effect on peer associations.